Biceps femoris architecture and strength in athletes with a previous anterior cruciate ligament reconstruction - Timmins, R. G.; Bourne, M. N.; Shield, A. J.; Williams, M. D.; Lorenzen, C.; Opar, D. A. (Medicine & Science in Sports & Exercise, 2016)
Purpose: This study aimed to determine whether limbs with a history of anterior cruciate ligament (ACL) injury reconstructed from the semitendinosus display different biceps femoris long head (BFlh) architecture and eccentric strength, assessed during the Nordic hamstring exercise, compared with the contralateral uninjured limb.